Variation and change in the short vowels of Delhi English. (March 2020) - Domange, Raphaël
Abstract: Although the sound system of Indian English has been the object of numerous publications over the years, there has been a remarkable scarcity of variationist sociolinguistic research carried out on the topic. The present study addresses this gap by describing the short front vowels of 22 lifelong English-speaking Delhi residents born between 1948 and 1992. Focusing more specifically on variation in the relative configuration of trap /æ/, dress /ɛ/, and kit /ɪ/, the study provides apparent-time evidence for a series of interrelated changes affecting the system. Those include an ongoing lowering of /æ/ and /ɛ/, as well as age-related variation in a previously unreported allophonic split of /ɪ/. I argue that these apparent-time patterns are amenable to an analysis in terms of chain shift, and I discuss the implications of such a claim, linking the phenomenon described to similar patterns reported in various other parts of the English-speaking world.